1992
DOI: 10.1073/pnas.89.24.11784
|View full text |Cite
|
Sign up to set email alerts
|

Human T-cell leukemia virus type I infection of monocytes and microglial cells in primary human cultures.

Abstract: The pathogenesis of progressive spastic paraparesis [HTLV-I-associated myelopathy/tropical spastic paraparesis (HAM/TSP)], a serious consequence of human T-cell leukemia virus type I (HTLV-I) infection, is unclear. T and B lymphocytes can be naturally infected by HTLV-I, but the susceptibility to HTLV-I infection of other cell types that could contribute to the pathogenesis of HAM/TSP has not been determined. We found that a human monocyte cell line (T]HP-1), primary human peripheral blood monocytes, and isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 44 publications
1
56
0
1
Order By: Relevance
“…Productive transmission of natural HTLV-1 isolates to primary human endothelial cell cultures (Ho et al, 1984;Hoxie et al, 1984), monocyte and microglial cells (Hoffman et al, 1992), as well as basal mammary epithelial cells (LeVasseur et al, 1998) has been reported.…”
Section: Htlv-1 Tropism: In Vitro or In Vivo Veritas?mentioning
confidence: 99%
“…Productive transmission of natural HTLV-1 isolates to primary human endothelial cell cultures (Ho et al, 1984;Hoxie et al, 1984), monocyte and microglial cells (Hoffman et al, 1992), as well as basal mammary epithelial cells (LeVasseur et al, 1998) has been reported.…”
Section: Htlv-1 Tropism: In Vitro or In Vivo Veritas?mentioning
confidence: 99%
“…First, cell-free infection by HTLV is very inefficient and efficient infection of cells requires cocultivation of peripheral blood mononuclear cells (PBMC) with irradiated HTLV-producer cells. Secondly, although HTLV has the capacity to infect a number of cell types including T cells, B cells, endothelial cells, glial cells, and monocytes of both human and nonhuman origin (Ho et al, 1984;Hoffman et al, 1984;Akagi et al, 1992;Koyanagi et al, 1993), the only cells susceptible to HTLV transformation are primary T lymphocytes. For the context of this article transformation is defined as continuous growth in the absence of exogenous IL-2; immortalization is defined as continuous IL-2-dependent growth.…”
Section: Htlv Experimental Systemmentioning
confidence: 99%
“…12,13 HTLV-1 enters CD4 ϩ and CD8 ϩ T cells, 14 whereas HTLV-2 infects preferentially CD8 ϩ T cells, though in patients with high proviral load both viruses can also integrate in monocytes and B cells. [15][16][17][18] The entry receptors used by these viruses have not yet been identified; experimental evidence suggests that the same receptor molecule (whose gene has been localized on chromosome 17, region q) may be shared by the 2 viruses. 19,20 T lymphocytes transformed in vitro by HTLV-1 21 and leukemic cells from patients with acute T-cell leukemia and lymphoma exhibit constitutive hyperactivation of signal transducer and activator of transcription (STAT) proteins, 22 a family of transcription factors essential for cytokine-regulated processes such as cellular proliferation, differentiation, and survival by the activation of downstream genes.…”
Section: Introductionmentioning
confidence: 99%